Đến nội dung


violympicioe

Đăng ký: 05-09-2015
Offline Đăng nhập: 07-05-2016 - 20:32
-----

#609398 $(a^3+b^3+c^3)(\frac{1}{a^3}+\frac{1...

Gửi bởi violympicioe trong 17-01-2016 - 10:27

$Bất\quad đẳng\quad thức\quad tg\quad đg\quad 3+\sum { \frac { { a }^{ 3 } }{ { b }^{ 3 } } +\sum { \frac { { b }^{ 3 } }{ { a }^{ 3 } }  }  } \ge \quad \frac { 3 }{ 2 } (\sum { (\frac { a }{ b } +\frac { b }{ a } ) } )\quad \\ Ta\quad sẽ\quad cm\quad 1+\frac { { a }^{ 3 } }{ { b }^{ 3 } } +\frac { b^{ 3 } }{ { a }^{ 3 } } \quad \ge \quad \frac { 3 }{ 2 } (\frac { a }{ b } +\frac { b }{ a } )\quad .\quad Thật\quad vậy\quad bđt\quad tg\quad đg\quad (\frac { a }{ b } +\frac { b }{ a } -2)({ (\frac { a }{ b } +\frac { b }{ a } ) }^{ 2 }+2(\frac { a }{ b } +\frac { b }{ a } )-1)\quad \ge \quad 0\\ luôn\quad đúng\quad ...$




#608131 Chứng minh rằng: $\sum \frac{a}{a^3+b^2+c}...

Gửi bởi violympicioe trong 09-01-2016 - 11:36

$Ta\quad có\quad \sum { \frac { a(\frac { 1 }{ a } +1+c) }{ { (a }^{ 3 }+{ b }^{ 2 }+c)(\frac { 1 }{ a } +1+c) }  } \le \sum { \frac { 1+a+ac }{ { (a+b+c) }^{ 2 } }  } \quad <=>\quad Ta\quad cần\quad cm\quad ab+bc+ac+6\quad \le \quad { (a+b+c) }^{ 2 }(1)\\ Lại\quad có\quad ab+bc+ac\quad \le \quad 3\quad (do\quad a+b+c=3)\quad (2).\quad Kết\quad hợp\quad (1)\quad và\quad (2)\quad ta\quad có\quad đpcm\quad \_ \quad dấu\quad "="\quad tại\quad a=b=c=1$




#608047 $\frac{a^2 +bc}{ac + b}+\frac{b^2 + c...

Gửi bởi violympicioe trong 08-01-2016 - 21:08

$Để\quad ý\quad rằng\quad 3ac+3b=3ac+b(a+b+c)=(ab+bc+ac)+({ b }^{ 2 }+2ac)\quad \le \quad ab+bc+ac\quad +{ a }^{ 2 }+{ b }^{ 2 }+{ c }^{ 2 }\quad \\ Tương\quad tự\quad ta\quad có\quad 3ab+3c\quad \le \quad { a }^{ 2 }+{ b }^{ 2 }+{ c }^{ 2 }\quad +ab+bc+ac\quad và\quad 3bc+3a\quad \le \quad { a }^{ 2 }+{ b }^{ 2 }+{ c }^{ 2 }+ab+bc+ac\\ Bđt\quad cần\quad cm\quad <=>\quad \sum { \frac { 3{ a }^{ 2 }+3bc }{ 3ac+3b }  } \ge \quad 3\quad \quad .\quad Sử\quad dụng\quad chú\quad ý\quad trên\quad ta\quad có\quad \sum { \frac { { 3a }^{ 2 }+3bc }{ 3ac+3b }  } \ge \quad \frac { 3\sum { { a }^{ 2 }+3\sum { ab }  }  }{ \sum { { a }^{ 2 }+\sum { ab }  }  } =3\\ =>\quad đpcm\quad .\quad Dấu\quad "="\quad tại\quad a=b=c=1$




#607757 $x,y,z>0$.Chứng minh:$\sum{\sqrt{x+yz...

Gửi bởi violympicioe trong 07-01-2016 - 16:09

$Đặt\quad \frac { 1 }{ a } =x;\frac { 1 }{ b } =y;\frac { 1 }{ c } =z\quad Ta\quad có\quad giả\quad thiết\quad \sum { x=1 } \quad Ta\quad cần\quad chứng\quad minh\quad :\quad \sum { \sqrt { x+yz }  } \ge \quad 1\quad +\quad \sum { \sqrt { xy }  } \\ Bđt\quad tương\quad đương\quad \sum { \sqrt { x(x+y+z)+yz }  } \ge \quad 1\quad +\quad \sum { \sqrt { xy }  } <=>\quad \sum { \sqrt { (x+y)(x+z) }  } \ge \quad 1+\sum { \sqrt { xy }  } \\ Áp\quad dụng\quad bđt\quad cauchy\quad schwarz\quad ta\quad có\quad \sqrt { (x+y)(x+z) } \ge \quad x+\sqrt { yz } .\quad Tương\quad tự\quad ta\quad có\quad đpcm.\\ Dấu\quad "="\quad tại\quad a=b=c=3$